New records and detailed distribution and abundance of selected arthropod species collected between 1999 and 2011 in Azorean native forests - Borges, Paulo A. V. (2018)
BACKGROUND: In this contribution we present detailed distribution and abundance data for arthropod species identified during the BALA – Biodiversity of Arthropods from the Laurisilva of the Azores (1999-2004) and BALA2 projects (2010-2011) from 18 native forest fragments in seven of the nine Azorean islands (all excluding Graciosa and Corvo islands, which have no native forest left). NEW INFORMATION: Of the total 286 species identified, 81% were captured between 1999 and 2000, a period during which only 39% of all the samples were collected. On average, arthropod richness for each island increased by 10% during the time frame of these projects. The classes Arachnida, Chilopoda and Diplopoda represent the most remarkable cases of new island records, with more than 30% of the records being novelties. This study stresses the need to expand the approaches applied in these projects to other habitats in the Azores, and more importantly to other less surveyed taxonomic groups (e.g. Diptera and Hymenoptera). These steps are fundamental for getting a more accurate assessment of biodiversity in the archipelago.